Kilka uwag o pomysłowości ("wit") u Locke’a - Załuski, Tomasz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2004)
The subject matter of the paper is an analysis of the role of 'wit' in J. Locke's "An Essay Concerning Human Understanding". The analysis shows that this apparently marginal issue plays in Locke's text ambivalent role. Interpreted by Locke as assemblage of ideas on the basis of their similarity, wit is, on the one hand, explicitly excluded from the domain of philosophy and situated within the sphere of aesthetic pleasure. On the other hand wit is an implicit constitutive element of a number of "Essay's" important philosophical issues, especially those of mind and of ideas formation. The analysis of wit may also be regarded as a contribution to the history of the philosophical treatment of wit and some related problems, such as inventiveness.